Pengaruh Cara Pengolahan Kakao Fermentasi dan Non Fermentasi Terhadap Kualitas, Harga Jual Produk pada Unit Usaha Produktif (UUP) Tunjung Sari, Kabupaten Tabanan - DAVIT M, JOHN; YUSUF, RIA PUSPA; YUDARI, DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
ABSTRACT Effect of Fermentation Cocoa Processing and Non Fermentation on The Quality and Pricing Products on Tunjung Sari Unit Produktive in Tabanan District The purpose of this study was to determine influence how a cocoa processing fermented and non fermented on the quality and price of the product and to determine constraints face on Tunjung Sari Unit Produktif in the processing of fermented and non- fermented cocoa on product quality and price . The method use  observation , interviews and literature study to record relevant information. then analyzed with descriptive and qualitative analysis. The results showed that the method of processing cocoa enough to affect the quality and price of products on Tunjung Sari unit Produktif. Processing cocoa bean fermentation yield account ( number of seeds ) 120 seeds per hundred grams while non fermented bean seeds acount 118 percent gram , fermented cocoa color to blackish brown in color while the non fermented brown light , aroma of cocoa beans have a distinctive fermentation processing chocolate aroma while the non- fermentation processing does not have a distinctive smell like chocolate , slaty ( purple beans ) fermented cocoa maximum of 3-5 %, while the non- fermented seeds no slaty ( purple beans ) slaty occur due to the fermentation process less than three days , in the form of fermentation of cocoa beans has a texture that is hollow while the non -textured solid fermentation , the level of moisture content of cocoa beans fermented 7 % and 7.5 % non- fermented and fermented cocoa beans price of Rp 19.500/kg while non fermented Rp 17.000/kg . Keywords: The effects of processing cocoa fermentation, Cocoa non fermentation, Q uality cocoa beans, Selling product.